2019
DOI: 10.3390/ijms20194904
|View full text |Cite
|
Sign up to set email alerts
|

piggyBac Transposon-Based Immortalization of Human Deciduous Tooth Dental Pulp Cells with Multipotency and Non-Tumorigenic Potential

Abstract: We aimed to immortalize primarily isolated human deciduous tooth-derived dental pulp cells (HDDPCs) by transfection with piggyBac (PB)-based transposon vectors carrying E7 from human papilloma virus 16 or complementary DNA (cDNA) encoding human telomerase reverse transcriptase (hTERT). HDDPCs were co-transfected with pTrans (conferring PB transposase expression) + pT-pac (conferring puromycin acetyltransferase expression) + pT-tdTomato (conferring tdTomato cDNA expression) and pT-E7 (conferring E7 expression) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 70 publications
0
18
0
Order By: Relevance
“…Therefore, there is a possibility that the~10% observed chromosome abnormalities could be an artifact caused by sample preparation for chromosome analysis. On the other hand, immortalization driven by the expression of TERT alone was recently reported in cell types related to the dental field, including dental pulp cells [28,29], human deciduous tooth dental pulp cells [30], and gingival fibroblasts [31]. Although we also tried to obtain immortalized dental pulp stem cells through the expression of TERT alone, we were unable to, even after confirming the successful integration of TERT into cells by PCR.…”
Section: Plos Onementioning
confidence: 80%
“…Therefore, there is a possibility that the~10% observed chromosome abnormalities could be an artifact caused by sample preparation for chromosome analysis. On the other hand, immortalization driven by the expression of TERT alone was recently reported in cell types related to the dental field, including dental pulp cells [28,29], human deciduous tooth dental pulp cells [30], and gingival fibroblasts [31]. Although we also tried to obtain immortalized dental pulp stem cells through the expression of TERT alone, we were unable to, even after confirming the successful integration of TERT into cells by PCR.…”
Section: Plos Onementioning
confidence: 80%
“…However, still quite often these two different groups of markers are found to be indistinctly mixed in the literature as an evidence of neuronal differentiation (e.g., a simultaneous rise of Nestin, Sox2 and MAP2 [ 109 ], or Nestin, β-3 tubulin and GFAP [ 110 ]). Even more problematic can be the use of non-specific labeling methods like Nissl stain [ 111 , 112 ], or the confusion that a mere rise in the expression of a particular neuronal marker (that is already substantially expressed by control hDPSCs) is taken as indicative of neuronal differentiation. Take for instance the case of the mature neuronal marker β-3 tubulin ( Figure 4 A).…”
Section: Neuronal-like Differentiation From Hdpscs: Problems and Cmentioning
confidence: 99%
“…The properties of HDDPCs isolated from several donors were previously examined at the immunocytological and molecular levels. It has been demonstrated that 1) expression levels of stemness factors [e.g., octamer-binding transcription factor 3/4 ( OCT3/4 ), sex determining region Y-box 2 ( SOX2 ), and ALP differ among the donors tested, 2) HDDPCs with high ALP activity and enriched with OCT3/4 and SOX2 tend to be easily reprogrammed into induced pluripotent stem cells when they are transfected with vectors carrying Yamanaka’s reprogramming factors, and 3) these ALP-enriched cells have the ability to differentiate into osteogenic or adipose cells when they are induced to differentiate into an osteoblastic or adipogenic lineage [ 13 , 14 ]. These findings suggested that ALP -positive cells (also positive for expression of OCT3/4 and SOX2 ) in HDDPCs could serve as a useful source in regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%